Pengaruh Dukungan Keluarga Terhadap Minat Belajar Pelajaran Agama Di MTs Muhammadiyah Salomekko Kabupaten Bone - Riswandi .; Alamsyah .; Rukiana Novianti Putri (CV. ITTC INDONESIA, 2025)
The Influence of Family Support on Interest in Learning Religious Studies at MTs Muhammadiyah Salomekko, Bone Regency. Supervised by Dr. Alamsyah., S.Pd.I., M.H and Rukiana Novianti Putri, S.Psi., M.Psi., Psychologist. This study aims to determine the relationship between family support and interest in learning religious studies among students at MTs Muhammadiyah Salomekko, Bone Regency. This study uses a quantitative approach with a correlational research type. The study population was all 20 students at MTs Muhammadiyah Salomekko. The sampling technique used was total sampling. Data collection was carried out using a family support questionnaire and a questionnaire on interest in learning religious studies. Data analysis used a simple regression correlation test with the help of the SPSS program version 23.0. The results of the study indicate that students' family support is in the moderate category (70%), and their interest in learning religious subjects is also in the moderate category (76.7%). The results of the simple regression correlation test show a calculated r value of -0.060 with a significance of 0.800 (> 0.05). Thus, it can be concluded that there is no significant relationship between family support and students' interest in learning religious subjects at MTs Muhammadiyah Salomekko, Bone Regency. The implications of this study indicate that increasing interest in learning religious subjects is not enough to rely only on family support, but requires the active role of teachers, schools, peer environments, and internal factors of the students themselves